SISTEM INFORMASI MANAJEMEN PENGOLAHAN DATA ASET MATERIAL PROMOSI MENGGUNAKAN QR CODE - Siswanto Siswanto; Maya Utami Dewi (STEKOM PRESS, 2020)
The development of smartphones today is very rapid and can not be separated in everyday life in finding information or making information and in all fields of work requires communication tools to access data and information, it is no wonder in terms of smartphone work being an inseparable part separate, this research I use smartphone especially Android which is currently one of the operational systems that are commonly used by the public especially Indonesia so that it can be used to help team performance in the field in this case Merchandiser in conducting Data Processing Asset Material Promotion Using Qr Code to monitor and control the allocation of promotional material assets in the field to facilitate reporting of promotional material assets. QR Code is a two-dimensional matrix code or barcode that comes from the word